1982
DOI: 10.1002/art.1780250107
|View full text |Cite
|
Sign up to set email alerts
|

Schönlein‐henoch syndrome in patients with familial mediterranean fever

Abstract: Ten episodes of Schonlein-Henoch purpura (SHP) in 8 patients with familial Mediterranean fever (FMF) were observed. Five episodes developed 3-14 days after penicillin injections, suggesting an etiologic association. FMF and SHP have clear clinical similarities, and if the frequency of association of the 2 diseases is indeed high, perhaps a common etiologic factor should be sought. An immune complex mechanism might be the link between these 2 disease entities.Familial Mediterranean fever (FMF) and Schonlein-Hen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
1
3

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 14 publications
1
54
1
3
Order By: Relevance
“…Current findings were different from the result obtained by Nikibakhsh et al, in which a high rate of M694V mutations in HSP subjects was reported (15). In contrast to the current findings, two other studies conducted by Altug et al and Bayram et al revealed the lower mutation rate for M694V in the HSP patient group (12,13). However, none of the patients with HSP showed the M694V mutation in a Chinese population (12).…”
Section: Resultscontrasting
confidence: 99%
“…Current findings were different from the result obtained by Nikibakhsh et al, in which a high rate of M694V mutations in HSP subjects was reported (15). In contrast to the current findings, two other studies conducted by Altug et al and Bayram et al revealed the lower mutation rate for M694V in the HSP patient group (12,13). However, none of the patients with HSP showed the M694V mutation in a Chinese population (12).…”
Section: Resultscontrasting
confidence: 99%
“…Acute mono arthritis usually appears spontaneously [4]. Some types of vasculitis are more frequent in FMF, including Henoch-Schönlein purpura (HSP) and Polyarteritis nodosa (PAN) [5]. Physical and emotional stress, hormonal changes (estrogen reduction, menstrual cycle etc.)…”
Section: Introductionmentioning
confidence: 99%
“…cisplatin) may trigger the FMF attacks. Chronic and protracted manifestations, particularly nephropathic amyloidosis, leading to chronic renal failure, chronic arthritis and protracted myalgia, may also occur in the disease [1,2,5].…”
Section: Introductionmentioning
confidence: 99%
“…1 -4 Renal failure in HSP as a result of progressive nephritis is the primary cause of mortality. 5 HSP may occur either as a primary disease or secondarily to other inflammatory diseases, such as familial Mediterranean fever, 6 polyarteritis nodosa and Behçet's disease.…”
Section: Introductionmentioning
confidence: 99%